HLA Antibody Incompatible Renal Transplantation: Long-term Outcomes Similar to Deceased Donor Transplantation. Issue 8 (19th July 2021) - Krishnan, Nithya; Abimbola, Aisha; Machan, Nandhini; Daga, Sunil; Gopalakrishnan, Kishore; Lam, ForTai; Tan, LamChin; Kashi, Habib; Imray, Christopher; Zehnder, Daniel; Collins, Claire; Curtis, Rebecca; et al.
Abstract : Background: HLA incompatible renal transplantation still remains one of best therapeutic options for a subgroup of patients who are highly sensitized and difficult to match but not much is known about its long-term graft and patient survival. Methods: One hundred thirty-four HLA incompatible renal transplantation patients from 2003 to 2018 with a median follow of 6.93 y were analyzed retrospectively to estimate patient and graft survivals. Outcomes were compared with groups defined by baseline crossmatch status and the type and timings of rejection episodes. Results: The overall patient survival was 95%, 90%, and 81%; and graft survival was 95%, 85%, and 70% at 1, 5, and 10 y, respectively. This was similar to the first-time deceased donor transplant cohort. The graft survival for pretreatment cytotoxic-dependent crossmatch (CDC) positive crossmatch group was significantly low at 83%, 64%, and 40% at 1, 5, and 10 y, respectively, compared with other groups (Bead/CDC, P  = 0.007; CDC/Flow, P  = 0.001; and microbead assay/flow cytometry crossmatch, P  = 0.837), although those with a low CDC titer (<1 in 2) have comparable outcomes to the CDC negative group. Female patients in general fared worse in both patient and graft survival outcomes in each of the 3 groups based on pretreatment crossmatch, although this did not reach statistical significance. Antibody-mediated rejection was the most frequent type of rejection with significant decline in graft survival by 10 y when compared with no rejection ( P  < 0.001). Rejection that occurred or continued to occur after the first 2 wk of transplantation caused a significant reduction in graft survivals ( P  < 0.001), whereas good outcomes were seen in those with a single early rejection episode. Conclusions: One-, 5-, and 10-y HLA incompatible graft and patient survival is comparable to deceased donor transplantation and can be further improved by excluding high-CDC titer cases. Antibody-positive female patients show worse long-term survival. Resolution of early rejection is associated with good long-term graft survival.